Setting Standards for Financial Reporting: FASB and the Struggle for Control of a Critical Process. - Zeff, Stephen A.; Boatsman, James R. (The Accounting Review, 1995)
Abstract Reviews the book `Setting Standards for Financial Reporting: FASB and the Struggle for Control of a Critical Process,' Robert Van Ripper.